Defeated by the System: The Structure and Significance of the Personal Stories of Hybrid Transition Losers - Dragana Antonijević (University of Belgrade, 2016)
This paper presents an analysis of the structure and an interpretation of personal and family stories about the loss of property, money, jobs and status in the period of blocked transformation or hybrid transition (a term proposed by the author), while also briefly outlining the reasons for the choice of the "hybrid" metaphor to describe the specific socio-economic, political and historical situation in Serbia in the 1990s. The theoretical basis for the analysis has been provided by the decades-long folkloristic and anthropological studies of personal stories and life histories, the analysis of the narrative structure of legends, and also by theoretical and practical analyses of the process of transition. The emphasis is on the study of losers’ narratives, through a referential and evaluative dimension, as a life experience in 1990s Serbia.